2008
DOI: 10.1002/eji.200737898
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 and S1P receptors cooperate to enhance inflammatory cytokine production in human gingival epithelial cells

Abstract: this process. One such cooperation between GPCR and TLR can be attributed to the sphingosine 1-phosphate (S1P) receptor family. The S1P receptors (S1P 1-5 ) are a family of GPCR with a high affinity for S1P, a serum-borne bioactive lipid associated with diverse biological activities such as inflammation and healing. In this study, we show that proinflammatory cytokine production, including IL-6 and IL-8, was increased with LPS and concomitant S1P stimulation. Furthermore, elevated cytokine production following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 38 publications
7
50
1
Order By: Relevance
“…Our results are in accordance with the cooperation of TLR4 and S1P receptors to enhance inflammatory cytokine production in human gingival epithelial cells (33). In contrast, in a previous study we have observed that TLR2 and S1P 1/2 receptors interaction resulted in the inhibition of chemokine production in human monocytes/ macrophages (20).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with the cooperation of TLR4 and S1P receptors to enhance inflammatory cytokine production in human gingival epithelial cells (33). In contrast, in a previous study we have observed that TLR2 and S1P 1/2 receptors interaction resulted in the inhibition of chemokine production in human monocytes/ macrophages (20).…”
Section: Discussionsupporting
confidence: 92%
“…Since functional TLR4 has been observed in GEC (20), the observation of CD14 in these cells and its induction by vitamin D supports its role in amplification of the innate immune defense. Another surprising gene we observed to be expressed in these cells was the gene encoding PPBP (also known as CXCL7).…”
Section: Discussionmentioning
confidence: 82%
“…In KB cells (a HeLa-like carcinoma cell line), however, P. gingivalis Rgp appears to activate PAR-1 and PAR-2 and release IL-6, a potent stimulator of osteoclast differentiation and bone resorption (Lourbakos et al, 2001a). Hence, the PAR-gingipain specificity leading to release of pro-inflammatory cytokines is unclear, in part complicated by the presence of P. gingivalis LPS with concomitant activation through Tolllike receptors (TLRs) also leading to expression of proinflammatory cytokines (Chen et al, 2008;Diya et al, 2008;Eskan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%